Developing a community-based model of care for venipuncture in children and young adults with an intellectual disability: a retrospective study - Pankaj Garg; Natasha Reid; Larissa Passarello; Catherine O'Hea; Teresa Lai; Bridget Farrell (BMJ Publishing Group, 2024)
Background Regular blood tests for monitoring metabolic side effects are often unable to be collected for people with an intellectual/developmental disability (ID/DD) and challenging behaviours (CBs) using usual pathways. We aimed to develop a model of care to facilitate venipuncture for children and young adults with ID/DD and CBs.Methods A systematic tiered model of care was developed for venipuncture to suit the individual needs of children and young adults with ID/DD and CBs. A partnership was formed by the disability health team with a community pathology service provider. An observational retrospective study of the baseline demographic data, severity of disability and diagnosis, oral sedation requirement, and outcome data on the success/failure of venipuncture was done.Results 14 children (mean (SD), 12.8 (3.1) years) had 17 attempted venipuncture with 'reasonable adjustments' such as preparation with social stories, distraction, low sensory strategies and oral sedation at school clinics. 14 (82%) attempts were successful. After the success of the pilot programme at school, venipuncture was replicated in settings such as home, day programmes, pathology centres and a respite facility. 16 people with ID/DD and CBs (mean (SD)17.3 (3.7) years), had 14 successful venipuncture performed out of 18 attempts (success rate, 77.7%). Overall, 11 attempts (31.4%) succeeded without requiring oral sedation using only reasonable adjustments. 16 attempts (45.7%) succeeded with conscious oral sedation along with reasonable adjustments. Of those 16, 10 required olanzapine (5 mg), 1 required olanzapine (10 mg), 1 required combination of risperidone (1 mg) and diazepam (5 mg), 1 required clonazepam (2.5 mg) and olanzapine (5 mg), 1 required combination of olanzapine (10 mg) and diazepam (10 mg), 1 required combination of olanzapine (10 mg) and diazepam (5 mg) while 1 required only diazepam (5 mg). One had to be switched to the tier-3 pathway.Conclusion A model of care was developed to ensure compassionate and non-stressful venipuncture for children and young adults with disabilities. We demonstrated that a significant proportion of carefully selected children and young adults with ID/DD and CBs, considered 'challenging for blood collection' can have venipuncture performed successfully in non-hospital settings using 'reasonable adjustments' and oral sedation.